How fathers construct and perform masculinity in a liminal prison space. (July 2019) - Bartlett, Tess S; Eriksson, Anna
Through a lens of identity and the self, this article analyses the views of 39 primary carer fathers incarcerated in Victoria focusing specifically on the points of intersection between fathers and their children. Using the prison visiting room and phone conversations by way of illustration it explores differing expressions of masculinity and seeks to understand the conflict of identity that exists for fathers within these liminal, in-between spaces. We aim to address a gap in research and theory by providing new insights into fathering and conflicting constructions of masculinity within the prison as seen in 'frontstage' and 'backstage' selves and by exploring how fathers perform fathering within this space. We conclude by summarising the key theoretical and practical implications of our work.